Adapting narrative exposure therapy with a tribal community: A community‐based approach. Issue 11 (27th May 2022) - Bedard‐Gilligan, Michele; Kaysen, Debra; Cordero, Rebeca Marin; Huh, David; Walker, Denise; Kaiser‐Schauer, Elisabeth; Robjant, Katy; Saluskin, Kathy; Pearson, Cynthia
Abstract: Objective: American Indian (AI) individuals are at increased risk for present‐day trauma exposure and associated negative outcomes, as well as ongoing effects of intergenerational trauma exposure and adversity. However, few empirically supported treatments exist that are specifically tailored and/or tested with AI communities. This study describes the process of selecting, adapting, and implementing narrative exposure therapy (NET) with an AI community. Methods: A community and academic partnership was formed and worked together to make culturally mindful changes to NET to best fit the needs of the community. The partnership incorporated community leaders/Elders ( n = 7), providers ( n = 11), and participants seeking treatment ( n = 50) to implement an iterative process of adapting and implementing the adapted form of NET. Results: Key adaptions included addressing historical and intergenerational trauma, greater protections for confidentiality in a small community, and incorporation of cultural customs and traditions. Overall, the adapted form of NET was favorably received by the participants, and the implementation appeared to be feasible, with improved retention over past trials of adapted trauma‐focused treatments with this community and with highly positive satisfaction ratings and feedback. Conclusions: NET was shown to be an appropriate approach for this AI community and should be considered as a treatment option for other AI communities. Future work should consider strategies outlined in this adaption as well as following a similar process for working with AI communities to implement culturally appropriate interventions for trauma‐related symptoms.